STATUS POPULASI BADAK SUMATERA DI DATARAN TINGGI KAPPI, KAWASAN EKOSISTEM LEUSER, PROVINSI ACEH - Rudi H Putra (Prosiding Seminar Nasional Biotik, 2018)
Kappi Plateau is one of the places in the Leuser Ecosystem where Sumatran rhinos are still found, but the quality of the population and its habitat is unknown. The purpose of this study is to determine the size of the existing population of Sumatran rhinoceros in Kappi, habitat quality and factors that affect the population in the study site. The research was conducted in the highlands Kappi Plateau in Gayo Lues district of Aceh province from August 2012 through August 2013. The methods used in data collection were direct observation and interviews. Study site was divided into 72 grid size of 4 km x 4 km. Data collected include findings of Sumatran rhinos, physical and biological conditions and human disturbance. This study has recorded 22 findings in 14 grid Sumatran rhino, with naive occupancy 0.194 and an estimated population of 8-14 individuals. One hundred fifty diet plant species was discovered in Kappi, with a distribution throughout the location, abundant water resources, and also there are six mineral resources supported by the dominant height of less than 1500 meters above sea level, the dominant slope is less than 40%. The evident shows threat of poaching and human disturbance suppressing the population. In the period 1964 - 1993 as many as 50 individual rhinos in Kappi were hunted by the surrounding community.